The Victimology of 10 Victims in The Novel "ثمّ لم يبق أحد" by Agatha Christie Based on the Perspective of Benjamin Mendelsohn - Widyasari, Rintina; Zawawi, Moh (TSAQOFIYA : Jurnal Pendidikan Bahasa dan Sastra Arab, 2024)
The murder victims in the novel ثمّ لم يبق أحد have their own dark secrets. They were invited to a house located on Warrior Island without the slightest suspicion. The invited victims have been targeted to be killed for what they did in the past. The purpose of this study is to describe the form of guilt of the victim according to the category of guilt in the novel ثمّ لم يبق أحد by Agatha Christie based on Mendelsohn's perspective. This type of research is descriptive qualitative. The primary data source used is Agatha Christie's novel ثمّ لم يبق أحد, while the secondary data source is articles, books and other literature sources on victimology studies. The data collection technique used is a reading and recording technique. The data analysis techniques used are data reduction, data presentation and conclusions. The findings in the novel "ثمّ لم يبق أحد " based on Mendelsohn's victimological perspective are known to have 3 categories of forms of victim guilt, namely: 1) the category of victims with a minimum level of guilt is found in 3 figures, namely Anthony Marston, Ethel Rogers and General MacArthur; 2) the category of guilt of the victim is the same as the perpetrator found in 4 figures namely Thomas Rogers, Emily Brent, Edward Armstrong, and Judge Wargrave; and 3) the category of victims with a greater degree of guilt than the perpetrator is found in 3 figures, namely William Blore, Philip Lombard and Vera Claythrone Abstrak Korban pembunuhan dalam novel ثمّ لم يبق أحد memiliki rahasia kelamnya masing-masing. Mereka diundang ke sebuah rumah yang berada di Pulau Prajurit tanpa curiga sedikitpun. Para korban yang diundang tersebut sudah ditargetkan untuk dibunuh atas apa yang mereka lakukan di masa lalu. Tujuan dari penelitian ini adalah mendeskripsikan bentuk kesalahan korban dalam novel ثمّ لم يبق أحد karya Agatha Christie berdasarkan perspektif Mendelsohn. Jenis penelitian ini adalah deskriptif kualitatif. Sumber data primer yang digunakan adalah novel ثمّ لم يبق أحد karya Agatha Christie, sedangkan sumber data sekunder adalah artikel, buku dan sumber literature lainnya tentang kajian viktimologi. Teknik pengumpulan data yang digunakan adalah teknik baca dan catat. Adapun teknik analisis data yang digunakan adalah reduksi data, penyajian data dan penarikan kesimpulan. Hasil temuan menunjukkan terdapat 3 kategori bentuk kesalahan korban yaitu: 1) kategori korban dengan kadar kesalahan minimal ditemukan dalam 3 tokoh yaitu Anthony Marston, Ethel Rogers dan Jenderal MacArthur; 2) kategori kesalahan korban sama dengan pelaku ditemukan dalam 4 tokoh yaitu Thomas Rogers, Emily Brent, Edward Amstrong, dan Hakim Wargrave; dan 3) kategori korban dengan kadar kesalahan lebih besar dari pelaku ditemukan dalam 3 tokoh yaitu William Blore, Philip Lombard dan Vera Claythrone